2000
DOI: 10.1007/s005920070005
|View full text |Cite
|
Sign up to set email alerts
|

Summer camps for diabetic children: an experience in Antalya, Turkey

Abstract: To evaluate the effectiveness of diabetic summer camps with objective parameters, we examined the data relative to summer camps organized by our department in Antalya in the last two years. The duration of the camps was 10 days. Twenty-eight diabetic children with an average age of 13.6 +/- 2.9 years (range 8-20) participated in the first camp, fourteen of whom participated in both camps. The medical personnel consisted of three pediatric endocrinologists, one psychologist, two diabetes nurses and two dietitia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(84 citation statements)
references
References 4 publications
7
73
0
4
Order By: Relevance
“…The intervention studies were also the oldest, having been conducted before the year 2000. In terms of participant characteristics, girls were the primary subjects in two studies, whereas four studies had an equal representation of boys and girls, and in one study gender was not reported (Semiz, Bilgin, Bundak, & Bircan, 2000). The age range varied from 4 to 18 years, but for those studies that reported the mean age, most focused on the preadolescent to adolescent years of 11–16 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The intervention studies were also the oldest, having been conducted before the year 2000. In terms of participant characteristics, girls were the primary subjects in two studies, whereas four studies had an equal representation of boys and girls, and in one study gender was not reported (Semiz, Bilgin, Bundak, & Bircan, 2000). The age range varied from 4 to 18 years, but for those studies that reported the mean age, most focused on the preadolescent to adolescent years of 11–16 years.…”
Section: Resultsmentioning
confidence: 99%
“…There were 28 adolescents enrolled, 8 of whom were overweight or obese. The mean weight loss was 0.9 kg after the first 10 days of camp (Semiz et al, 2000). Gender and statistical significance of the weight loss or sustainability was not reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Obserwacje poczynione na stosunkowo krót-kich 5-7-dniowych turnusach wakacyjnych podkreślają, poza walorami edukacyjnymi i poprawą samokontroli [13][14][15], także wzrost u dzieci i nastolatków akceptacji choroby i wzrost adaptacji do codziennego życia [16,17].…”
Section: Dyskusjaunclassified